Electrophysiological Correlates of Basic and Higher Order Cognitive and Affective Theory of Mind Processing in Emerging and Early Adulthood—An Explorative Event-Related Potentials Study to Investigate First-, Second-, and Third-Order Theory of Mind Processing Based on Visual Cues - Tesar, Benjamin; Deckert, Matthias; Schmoeger, Michaela; Willinger, Ulrike (Frontiers in Human Neuroscience, 2020)
Attributing mental states to others in social interactions (Theory of Mind - ToM) often depends on visual social cues like eye gaze or mimic. This study presents an event-related potentials task (Brainy-ERP) that was developed in order to investigate the electrophysiological correlates of first, second, and third-order cognitive and affective ToM processing. The task was based on social visual cues and involved ERP-analyses and eLORETA source localization analyses. Results showed that in cognitive and affective conditions, first order trials elicited greater Anterior P2 (180-370ms) amplitudes. In the cognitive condition, third order trials elicited greatest amplitudes in the broadly distributed Early Negative Slow Wave (eNSW, 260-470ms) and the Late Negative Slow Wave (LNSW, 460-1000ms). In the affective condition, third order and second order trials elicited greatest amplitudes in a broadly distributed Negative Slow Wave (NSW, 250-1000ms). Regarding affective trials in the NSW time span, statistical significant differences and trends were shown regarding activation of underlying brain regions. Third order trials elicited greatest activation in a number of regions typically associated with the ToM-network, especially the PCC, Cuneus, and TPJ. Furthermore, ToM low performer (participants with high accuracy but longer reaction times) showed by trend smaller Posterior N1 and significantly smaller eNSW amplitudes compared to average and high performer. This study offers new insights into electrophysiological correlates of basic and higher order cognitive and affective ToM processing, and its precise time course.